THE IMPACT OF AUDIT QUALITY ON AUDITOR MORAL REASONING, COMPETENCE AND INDEPENDENCE ON PROFESSIONALISM IN PUBLIC ACCOUNTING OFFICE - Rita Andini; Dheasey Amboningty (Jurnal Scientia, 2023)
This study aims to examine Job Assessment, Professionalism and Skills on Employee Performance. This research was conducted at SMEs. The population of this study were employees of the weaving department at SMEs. The sampling method used purposive sampling by distributing questionnaires to employees in the weaving department and conducting interviews. The data analysis technique used is multiple linear regression analysis.The results showed that Job and Skills Assessment had a significant positive effect on Employee Performance. Professionalism has no significant positive effect on employee performance. Job Assessment, Professionalism and Skills have a positive effect simultaneously on Employee Performance.